Ukuma njenge ndoda: the making of Xhosa masculinities in Mthatha, Eastern Cape - Silosini, Tandokazi (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This study examines how young men construct their masculine identities in daily life through the collection of activities that happen throughout young men's lives in Mthatha, Eastern Cape. The aim of the research is to examine how black men construct their identity as men. It seeks to examine the everyday ways in which young men speak of their masculinity, how they understand themselves in relation to women and the causes of gender-based and sexual violence in South Africa. The study conceptualises Xhosa masculinities and manhood within the framework of masculinist violence and the state. It demonstrates the intersection of manhood violence and the state within the discipline of international relations which is characterised by ideas of state security and war. Interviews with Xhosa men in Mthatha illuminated that boys are raised to be men who stand, articulated as ukuma njenge ndoda (standing up as a man), for themselves, family and community. Ukuma operates as an assertion and protection of self, a demonstration of independence and being self-sustaining. It importantly speaks to the gendered division of labour where over and above standing up for oneself, it is a man's duty and responsibility "ukumela izinto zekhaya" "“ to stand up for his home and family. This thesis shows that the different forms that ukuma carry with them expectations of dominance and control or at least maintain the appearance of it. Ultimately, the concept of ukuma serves as a way to legitimise the use of force or violence in certain instances where men feel that an act of violence constitutes ukuzimela (standing up for himself) or ukumela ikhaya (standing up for his family). The masculinising of this duty implicates not only the men it is bestowed upon the women and children who are the ones supposedly protected and provided for.
Keywords: Xhosa (African people) -- South Africa Mthatha; Men, Black -- South Africa Mthatha; Men Identity; Masculinity; Gender-based violence